Development of Inquiry-Based E-Modules Integrated with STEM in Stoichiometry Material to Improve Creative Thinking Skills and Learning Motivation - Assari, Andra Meisantry; Aznam, Nurfina (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This research aims to develop an integrated STEM inquiry-based e-module on stoichiometry material to enhance creative thinking skills and learning motivation among high school students, that is feasible, practical, and effective. This study employed a research and development (R&D) method with the 4D model, involving four stages: define, design, develop, and disseminate. The research subjects were 72 students at SMA Negeri 7 Pontianak, selected using cluster random sampling, with a quasi-experimental design with a control group. Data collection techniques included non-test and test methods. Data analysis techniques included qualitative analysis of interview results and feedback, and quantitative analysis of score acquisition. The results showed: (1) an interactive e-module using a STEM-integrated inquiry approach; (2) very feasible quality in terms of material and media, with an average score of 144 out of 160; (3) excellent practicality quality with an average score of 71 out of 80; (4) excellent readability with an average score of 46.22 out of 52; (5) a significant difference in creative thinking ability and learning motivation simultaneously and respectively, with a significance value of 0.000 < 0.05; and (6) the effective contribution of using e-modules to increase creative thinking ability and learning motivation simultaneously by 48.4%, and respectively by 14.8% (creative thinking ability) and 44.0% (learning motivation). The implications of the research show that the use of e-modules significantly improves students’ creative thinking skills and motivation, supports teachers in teaching stoichiometry interactively and contextually, and enriches learning media and digital teaching materials for the 21st-century curriculum.